Effects of motivational music on psychophysiology measurements during moderate intensity exercise - Malik, Adam Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
The purpose of this study was to examine the effects of motivational music during moderate intensity exercise on psycho-physiological measurements including heart rate, recovery time, rate of perceived exertion (RPE), duration of exercise and post exercise feeling (EFI). A total of ten healthy male subjects of Universiti Sains Malaysia students (22.6 ± 0.7 years old) were involved in this study. Brunel Motivational Rating Inventory-2 (BMRI-2) was used to determine the list of motivational musics. In pre-experiment, subjects performed two preliminary test, which are sub-maximal running test and maximal oxygen test the determination of 65% of VO2 max intensity exercise. Experiment involved three different exercise conditions were performed by the subjects; exercise with motivational music, exercise with oudeterous music and exercise with no music. Measurements on heart rate and RPE were recorded during experiment, while recovery time, exercise duration and feeling were assessed after experiment completed. The findings revealed a significant difference (p=.011) for exercise duration in exercise with motivational music compared to the other groups. There was also significant result (p=.O29) for feeling (positive engagement) in exercise with motivational music compared to Control group. There was no significant difference for recovery time, heart rate, RPE and three others subscale of EFI (tranquillity, revitalization and physical exhaustion) among the three exercise conditions. The results supported most of the previous findings on the positive effect of music especially on physiological